Cardiovascular Organ Damage in Clinical Subtypes of Systemic Sclerosis: Arterial Stiffness and Echocardiography Might Not Be the Ideal Tools for Patient Risk Stratification - Eleonora Avenatti; Giulia Bruno; Marta Priora; Simone Parisi; Chiara Ballini; Franco Veglio; Alberto Milan; Enrico Fusaro (Cardiology Research and Practice)
Background. Vascular damage is recognized as a diagnostic landmark in systemic sclerosis (SSc), both in its limited and diffuse subtypes. Early detection at a subclinical stage with transthoracic echocardiography (TTE) and carotid femoral pulse wave velocity (cfPWV) may be helpful in therapeutic planning and management. Aim of the Study. The aim of the study was to evaluate presence of subclinical cardiovascular damage in patients with limited and diffuse SSc in comparison with a cohort of healthy individuals. Methods. Consecutive patients with limited and diffuse SSc underwent complete TTE and cfPWV and a complete review of clinical data. As controls, 23 healthy subjects with similar hemodynamic profiles were selected. Results. 41 patients (35 female, aged 56.9 years), 21 with diffuse and 20 with limited SSc, were recruited. Past medical history, cardiovascular risk factors, gender distribution, and disease duration were similar in the two groups as well as TTE parameters and hemodynamic indexes—cfPWV (6.5 [6–6.8] vs. 7.0 [6.2–8.5], p=0.24) and augmentation index (145.6 ± 14.2 vs. 149 ± 20.6, p=0.52). Patients with limited SSc were 10 years older than patients with diffuse SSc. In the multiple regression analysis, only age (p=0.0154) and disease duration (p=0.0467) resulted as the significant determinant of cfPWV. When compared to healthy controls, no significant difference emerged in TTE or hemodynamic indexes. Conclusion. In SSc, cfPWV increases with age, with no additional impact of pathology or subtype. Vascular damage in the SSc population is not accurately reflected in increased arterial stiffness, as evaluated with cfPWV, or classically defined echocardiographic findings of organ damage (i.e., left ventricular concentric remodelling and increased filling pressures).